2017
DOI: 10.15666/aeer/1503_001014
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Potassium Quantity/Intensity Properties of Selected South African Soils (Kwazulu-Natal) and Their Correlation With Selected Soil Parameters

Abstract: Nongqwenga -Modi: Phosphorus and potassium quantity/intensity properties of selected South African soils - Abstract There is no general single state function which describes the uptake of phosphorus (P) or potassium (K) by crop or escape in agro-ecosystem as a function external application. It is however proposed that quantity intensity relations have a potential of explaining such a paradigm. Extrapolating parameters from Quantity/Intensity (Q/I) parameters is laborious and technically complex, which makes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Studies have shown that P is low in South African soils [6]. The challenges of low P are associated with its limited mobility in the soil, due to high adsorption, and hence its unavailability [7] and fixation [8], thus contributing to its deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that P is low in South African soils [6]. The challenges of low P are associated with its limited mobility in the soil, due to high adsorption, and hence its unavailability [7] and fixation [8], thus contributing to its deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) is one of the important essential nutrient elements for crop production (Nkaa et al 2014;Nongqwenga and Modi 2017) due to its significant role in numerous plant processes including photosynthesis, respiration, cell division and energy transformation (Karikari et al 2015). The work of Adeyemi et al (2020) and Namakka et al (2017) revealed that P plays an important role in the growth, seed development, nitrogen fixation of cowpea and overall yield of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…People are closely followingwatching the potential of acid protease (Liu et al 2004, Zhang et al 2009, Yu et al 2006, Wang et al 1993, Mi et al 2017, Ali and Iftikhar 2017, Shamsudin et al 2017. Acid protease is mainly obtained through microbial fermentation currently, which can be generated by Aspergillus niger, Aspergillus oryzae, Bacillus, etc (Shen et al 1999, Nongqwenga andModi 2017). Aspergillus niger is the most commonly used fungus for producing acid protease due to it is less toxic and generates more metabolites.…”
Section: Introductionmentioning
confidence: 99%